Heavy metals leaching of MSWI bottom ash: effect of short-term natural weathering - Seniūnaitė, Jurgita; Vasarevičius, Saulius (International Conference “Environmental Engineering”, 2017)
Municipal solid wastes incineration (MSWI) is an important part of the waste management systems in many European countries. Incineration process generates two main by roducts: fly ash (FA) and bottom ash (BA). Bottom ash is composed of a variety of oxides, heavy metals and salts. Landfilling of untreated (fresh) BA can cause soil, surface and ground water contamination problems, because atmospheric precipitation in BA formed leachate, which contains of various materials. In this study investigates the influence of natural weathering to heavy metals leaching from BA. Leaching tests of bottom ash were carried out in 6 months, leachate samples were taken at 12 times (every 2 weeks). Heavy metals (Pb, Cu) concentrations were determined by atomic adsorption of spectral analysis method. The research shown, that the highest lead and copper concentration was determinated in 2 weeks weathered bottom ash leachate, respectively was 0.613 mg l–1 and 0.068 mg l–1. In both cases the concentration of Pb (0.010–0.052 mg l–1) and Cu (0.0100.018 mg l–1) became almost stable after 12 weeks. Can be concluded, that short erm (3 months) natural weathering is sufficient time for stabilise MSWI bottom ash and heavy metals (Cu and Pb) leaching. After 18–24 weeks heavy metals concentrations stabilized and remained almost constant.